Virtual reality as the indicator of the modern banking - Kołodziej, Monika (Wirtualna rzeczywistość jako wyznacznik nowoczesnej bankowości, 2017)
The dynamism of changes occurring in the social-economic space determines need for the systematic development, understood as seeking innovative solutions. Given that 46% of the world population uses the Internet and the 31% declares that they are active users of social media, no rationally formulated corporate strategy can omit the potential of computer technologies. One of the advanced solutions which are successively adapted in the sector of banking services is virtual reality. It seems that every industry from video games developers to healthcare is looking for innovative ways to integrate some sort of virtual reality platform into their day-to-day systems. The aim of the article is the presentation of the concept of virtual reality in the context of banking. The article proves the implementation of VR in banking generates competitive advantage. Additionally, it presents various aspects of applications, market trends and forecasts of the subsequent development of this phenomenon. Moreover, there is an attempt to answer a question, whether virtual reality improves the effectiveness of the banking activity
Nauki o Finansach = Financial Sciences, 2017, Nr 2 (31), s. 44-51
Keywords: virtual reality; banking; innovation; information technologies; wirtualna rzeczywistość; bankowość; innowacja; technologie informatyczne